Breakdowns, (Un-)Sichtbarkeiten und glitches. Kritische Geographien der Resilienz digitaler Infrastrukturen - Michel, Boris; Dammann, Finn (Geographica Helvetica, 2024)
This paper draws on current discussions in digital geography that emphasize the political and theoretical role of glitches. While we sympathize with the basic assumptions of this discussion and also find it helpful to connect these to older discussions around digital infrastructures, we propose an opposing perspective with this text. Using the example of Internet infrastructures, we focus on the continuous and painstaking work of making infrastructures invisible and preventing glitches. We are particularly interested in the production of resilience and focus from a geographical perspective on the rationalities of redundancy and addressing latenc

Contested Spatialities of Digital Sovereignty - Glasze, Georg; Cattaruzza, Amaël; Douzet, Frédérick; Dammann, Finn; Bertran, Marie-Gabrielle; Bômont, Clotilde; Braun, Matthias; Danet, Didier; Desforges, Alix; Géry, Aude; Grumbach, Stéphane; Hummel, Patrick; et al. (Geopolitics, 2023)
“Digital sovereignty” has become a buzzword in digital policies. Contrary to the imaginary of digital transformation as preceding an era of limitless global networking in the 1990s, approaches to state regulation and delimitation of data flows as well as programmes for national digital infrastructures are justified with calls for digital sovereignty across very different contexts. This forum brings together contributions from political geography, law, computer science, and ethics that compare and analyse discourses and practices of digital sovereignty. The case studies on Russia and the EU reveal parallels as well as fundamental differences in the conception and implementation of digital sovereignty. Essays on the challenges posed by new forms of cross-border interaction (such as cloud computing) and new actors (such as digital platforms) illustrate that the traditional coupling of concepts of sovereignty, territoriality and the state, of jurisdiction and borders, must be rethought. The essays in this forum thus make it clear that the digital transformation is not simply a socio-technical modernisation process. It is rather shaped in specific ways and should be understood and analysed as (geo)-political discourses and practices. The forum contributes to the development of a political digital geography that analyses how the digital transformation is contested and produced in specific ways and unearths the politics and spatialities conceived and produced in these discourses and practices.<br

Das Subjekt im politischen Diskurs zu „digitaler Souveränität“ - Pohle, Julia; Thüer, Leo; Dammann, Finn; Winkler, Jan (Handbuch Digitalisierung und politische Beteiligung, 2022)

De/colonizing OpenStreetMap? Local mappers, humanitarian and commercial actors and the changing modes of collaborative mapping - Schröder-Bergen, Susanne; Glasze, Georg; Michel, Boris; Dammann, Finn (Geo Journal, 2022)
In its early days, the geodata and mapping project OpenStreetMap (OSM) was widely celebrated for opening up and “democratizing” the production of geographic knowledge. However, critical research highlights that the new socio-technical practices of collaborative mapping often also produce or reproduce patterns of exclusion, not least in the area of relative data density between the Global South and North. These findings notwithstanding, we consider it important to acknowledge the increasing number of contributions of geodata from regions outside the old European core of OSM. This expansion of geodata production in OSM is related to a diversification of OSM actors and socio-technical practices. While OSM has often been described as a crowd-based project bringing together thousands of individual craft mappers, our analysis of OSM metadata indicates new institutional actors are gaining relevance. These developments have not only resulted in new collaborations but also conflicts between local mapping communities and institutional actors. We interpret these processes in two ways. First, the expansion of mapping activities can be viewed as a decolonizing process, whereby quantitative differences in data density between the Global North and South are partly reduced and new groups of local mappers are empowered to produce geographic knowledge. Second, these new developments can also be understood as colonizing processes. The engagement of large commercial actors in OSM raises concerns that the project (and its local mappers) could be used as a new means of data extraction and that in particular new and diverse voices in the OSM community are marginalized by a fixation on economically exploitable, modernistic and universalistic epistemologies. However, this supposedly clear distinction should not obscure the fact that colonizing and decolonizing processes intertwine in complex ways.
Keywords: Critical cartography; OpenStreetMap; Volunteered geographic information; Local knowledge; Geoweb; Data extractivism; Digital commons

Digitale Ungleichheiten überwinden – kritisches Kartieren crowdbasierter Wissensproduktionen - Dammann, Finn; Michel, Boris (Handbuch Kritisches Kartieren, 2022)

Digitally competent – digitally sovereign – digitally civic: geopolitics of subject formation in the German context - Winkler, Jan; Dammann, Finn (Geopolitics, 2022)

Geographical Research in the Digital Humanities. Spatial Concepts, Approaches and Methods - Dammann, Finn; Kremer, Dominik ([transcript] Bielefeld University Press, 2024)

Geographies of “digital governmentality” platform-based governing through adaptive environments - Dammann, Finn; Eichenmüller, Christian; Glasze, Georg (Digital Geography and Society, 2022)
In this paper, we discuss the geography of a new digital governmentality. In recent years, and extending Foucauldian analyses of different modes of governing, several studies argue that the digital transformation is fundamentally changing the way people are governed and govern themselves: a new, digital governmentality is emerging and replacing (neo-)liberal forms of governing. Two core characteristics are described as the basic nexus of this shift: on the one hand, a change in knowledge production through the capture and analysis of behavioural data; and on the other hand, a change in the governing of subjects by influencing subconscious behavioural patterns. We show that the perspective of a digital governmentality can sensitise geography to this new mode of digital governing. Furthermore, the digital governmentality debate enables geography to explore interconnections within the power/knowledge nexus between different aspects of the digital transformation that have so far been analysed in rather isolated ways. At the same time, geographic inquiries in turn offer impulses for the digital governmentality debate: Firstly, scholarly debate on a digital governmentality has rarely addressed the geographies in and through which this new governmentality operates. Addressing this research desideratum, we conceive two interconnected geographies of a digital governmentality and combine them into an analytical perspective: a new micro-geography of hybrid, sensing, and adaptive environments and a new macro-geography of digital platforms. Secondly, this perspective contributes to unearth the complex, often contradictory and contested relationships of a digital governmentality to other modes of governing. We use this perspective on geographies of digital governmentality to understand the development of digital outdoor advertising by Europe's largest out-of-home advertising company.<br
Keywords: Digital governmentality; Platforms; Environmentality; Digital geographies; Smart city; Nudging

Governing digital circulation: the quest for data control and sovereignty in Germany - Dammann, Finn; Glasze, Georg (Territory, Politics, Governance, 2022)
How is the circulation of digital data to be governed? This question is the subject of often conflicting political rationalities. Focusing on internet and data politics in Germany, we identify fundamental problematizations in governing data circulation on the basis of a mixed-methods analysis of the public–political discussion. In doing so, we elaborate the genealogy of a tension between two political rationalities. On the one hand, there are the political rationalities of a global information society since the 1990s. These have propelled the free circulation of data across national borders and Germany’s integration into an international and competitive telecommunications and information technology market. In these rationalities, state intervention in the circulation of data is seen as a dangerous obstacle to economic competitiveness and social prosperity. On the other hand, there are the political rationalities of a digitally sovereign statehood since the early 2010s. These consider state intervention in data circulation as a guarantor of economic prosperity, democracy and the ability to govern. We argue that prominent political technologies of territorial regulation of data circulation currently discussed and experimented within Germany can be interpreted as attempts to harmonize this field of tension.<br
Keywords: Germany; territory; digital sovereignty; data politics; digital circulation; data flows

Handbuch Kritisches Kartieren - Dammann, Finn; Michel, Boris (transcript, 2022)

Kritisches Kartieren – zur Einführung - Dammann, Finn; Michel, Boris (Handbuch Kritisches Kartieren, 2022)

Politische Geographien der digitalen Transformation – Von der „globalen Informationsgesellschaft“ zur „digitalen Souveränität“ - Dammann, Finn; Glasze, Georg (Bayreuther Kontaktstudium Geographie, 2023)
Keywords: Digitale Geographie; Informationsgesellschaft; Digitale Transformation; Internet Governance

Regieren und Steuern - Dammann, Finn; Glasze, Georg (Handbuch Digitale Geographien, 2021)
Eine Politische Digitale Geographie untersucht, wie mit digitalen Techniken gesellschaftliche Raumverhältnisse verändert und damit Gesellschaften durch Digitalisierung in spezifischer Weise gesteuert werden. Darüber hinaus fasst sie die digitale Transformation grundlegend als einen gestalteten, potenziell umstrittenen, machtvollen und in diesem Sinne politischen Prozess. Aus einer solchen Perspektive heraus fragt sie, wie die digitale Transformation im politischen Denken geformt und in der politischen Praxis gestaltet wird - und nicht zuletzt, welche Raumkonzepte sich in eine solche Steuerung von Digitalisierung einschreiben

Spatial concepts, approaches and methods for digital humanities-an introduction to the book - Dammann, Finn; Kremer, Dominik (Bielefeld University, 2024)
CRIS-Team Scopus Importer:2024-04-12

Spatial Concepts, Approaches and Methods for Digital Humanities – An Introduction to the Book - Dammann, Finn; Kremer, Dominik (Geographical Research in the Digital Humanities. Spatial Concepts, Approaches and Methods, 2024)

Verfahren der lexikometrisch-compterlinguistischen Analyse von Textkorpora. - Dammann, Finn; Glasze, Georg; Dzudzek, Iris; Mattissek, Annika; Schirmel, Henning (Handbuch für Diskurs und Raum. Theorien und Methoden für die Humangeographie sowie die sozial- und kulturwissenschaftliche Raumforschung, 2021)

Von der „globalen Informationsgesellschaft“ zum „Schengenraum für Daten“ – Raumkonzepte in der Regierung der „digitalen Transformation“ in Deutschland - Glasze, Georg; Dammann, Finn (Räume digitaler Kommunikation, 2021)
Ausgangspunkt des Beitrages ist die Beobachtung, dass in politischen Auseinandersetzungen mit der „digitalen Transformation“ in Deutschland seit den 2010er Jahren vermehrt das Schlagwort einer „digitalen Souveränität“ auftaucht. In diesem Kontext werden vielfach Konzepte von staatlicher Eigenständigkeit und territorialer Abgrenzung mit dem Themenfeld der digitalen Transformation verknüpft. Diese Verknüpfung muss verwundern, da bis vor wenigen Jahren die Verbreitung digitaler Techniken sowohl in der wissenschaftlichen Auseinandersetzung als auch in politischen Debatten überwiegend als Element und Antreiber von Vernetzung, Überwindung von Grenzen und Globalisierung gerahmt wurde – also nicht mit einer territorialen, sondern mit einer entgrenzt-globalen Räumlichkeit verknüpft wurde. Die Räumlichkeit gesellschaftlicher Prozesse wurde lange Zeit vielfach nur als gegebener Kontext betrachtet und wenig hinterfragt. Mit der Hinwendung zu konstruktivistischen Raumkonzepten in der Geographie seit den 1980er Jahren sowie seit Ende der 1990er Jahre mit der Debatte um einen spatial turn teilweise auch in den benachbarten Sozial- und Kulturwissenschaften, rückten aber Fragen nach der semantischen sowie materiell-praktischen Herstellung von Räumen verstärkt ins Blickfeld der wissenschaftlichen Debatte. Die neuere Politische Geographie fragt dementsprechend danach, wie die Herstellung bestimmter Räume Baustein einer (Re-)Produktion spezifischer gesellschaftlicher Wirklichkeiten und in diesem Sinne politisch ist. Diese Forschungsfrage wendet der vorliegende Beitrag auf das Feld der digitalen Transformation an. Vor dem Hintergrund der „Verwunderung“ über die Forderungen nach territorialer Schließung in den Debatten einer digitalen Souveränität untersuchen wir, welche Räumlichkeiten in den politischen Diskursen im weiten Themenfeld der Digitalisierung seit den 1990er Jahren entworfen wurden, und wie diese Räumlichkeiten vor dem Hintergrund spezifischer Problematisierungen der digitalen Transformation zu Bestandteilen politischer Programme und Techniken wurden und aktuell werden
Keywords: Digitale Souveränität; Politische Geographie; Digitale Transformation; Netzpolitik; Territorialisierung

»Wir müssen als Deutsche und Europäer unsere digitale Souveränität zurückgewinnen!« Historische Rekonstruktion und internationale Kontextualisierung der Diskurse einer »digitalen Souveränität« in Deutschland - Dammann, Finn; Glasze, Georg (Was heißt digitale Souveränität? Diskurse, Praktiken und Voraussetzungen »individueller« und »staatlicher Souveränität« im digitalen Zeitalter, 2022)
Digitale Souveränität« hat sich in den 2010er-und 2020er-Jahren zu dem zentralen Leitmotiv nationaler und internationaler Digitalpolitik entwickelt. Auch in den politisch-öffentlichen Diskursen in Deutschland werden seither vielfach Ansätze einer »digitalen Souveränität« aufgegriffen – und dies in ganz unterschiedlichen gesellschaftlichen Bereichen. Diese Rückbesinnung auf Souveränität über digitale Informations- und Kommunikationssysteme muss zunächst verwundern, war die deutsche Telekommunikationspolitik doch seit den frühen 1990er-Jahren geprägt von Vorstellungen eines »schlanken Staates« und einer Überwindung nationaler Grenzen hin zu einer »globalen Informationsgesellschaft«. Gerade ein Beharren auf Prinzipien staatlich-territorialer Souveränität galt als überholt und wurde vielfach kritisiert. Wie lässt sich vor diesem Hintergrund die Rezeption von »digitaler Souveränität« in den 2010er-Jahren in Deutschland erklären? Zur Beantwortung dieser Fragen rekonstruieren wir in diesem Beitrag ausgehend von der Kommerzialisierung des Internets in den 1990er-Jahren bis in die frühen 2020er-Jahre jene historischen Brüche und (Dis-)Kontinuitäten im digitalpolitischen Diskurs, die zur Konsolidierung einer spezifischen Diskursformation rund um das Schlagwort »digitale Souveränität« in Deutschland beigetragen haben – und situieren diese in den internationalen Kontex

Wissen durch Karten - Glasze, Georg; Dammann, Finn; Bauer, Lea (Handbuch Digitale Geographien, 2021)
Karten sind mit den Worten David Harveys eine zentrale „Säule“ jeglichen geographischen Wissens (2001, S. 217). Die sozial- und kulturgeographische Auseinandersetzung mit Karten fragt danach, welches geographische Wissen mit und in Karten vermittelt wird (und welches nicht), auf welche Weise und von wem Karten produziert und genutzt werden sowie nicht zuletzt, wie Karten als Bausteine größerer sozio-technischer Zusammenhänge analysiert werden können. <